Detection of influenza A and B with the Alere™ i Influenza A & B: a novel isothermal nucleic acid amplification assay. Issue 3 (27th February 2015) - Hazelton, Briony; Gray, Timothy; Ho, Jennifer; Ratnamohan, V. Mala; Dwyer, Dominic E.; Kok, Jen
Abstract : Background: Rapid influenza diagnostic tests (RIDTs) have an important role in clinical decision‐making; however, the performances of currently available assays vary widely. Objectives: We evaluated the performance of the Alere ™ i Influenza A&B (Alere ™ iNAT), a rapid isothermal nucleic acid amplification assay that has recently received FDA clearance, for the detection of influenza A and B viruses during the Australian influenza season of 2013. Results were compared to two other RIDTs tested in parallel; Quidel Sofia ® Influenza A+B fluorescent immunoassay (FIA) and Alere ™ BinaxNOW ® Influenza A & B immunochromatographic (ICT) assay. Methods: A total of 202 paired nasopharyngeal swabs collected from patients ≥16 years old with an influenza‐like illness (ILI) were eluted in 2 ml of universal transport medium (UTM) that was used to perform all three RIDTs in parallel. Reverse‐transcription polymerase chain reaction (RT‐PCR) was used as the reference standard. Results: Compared to RT‐PCR, Alere ™ iNAT detected 77·8% influenza A positive samples versus 71·4% and 44·4% for the Quidel Sofia ® Influenza A+B FIA and BinaxNOW ® Influenza A & B ICT assay, respectively. For influenza B, Alere ™ iNAT detected 75% of those positive by RT‐PCR, versus 33·3% and 25·0% for Sofia ® and BinaxNOW ®, respectively. The specificity of Alere ™ iNAT was 100% for influenza A and 99% for influenza B. Conclusions: Alere ™ i Influenza A&B is a promising new rapid influenza diagnostic assay with potential point‐of‐care applications.